Norovirus as cause of severe gastroenteritis among children admitted in a pediatric hospital in Bel?m, Par?, Brazil - Siqueira, J. A. M (Sociedade Brasileira de Virologia, 2018)
Trabalho apresentado no Annals of National Meeting of Virology, XXI., 2010, Gramado, Rio Grande do Sul.